Applicability of Pulsed Electric Field (PEF) Pre-Treatment for a Convective Two-Step Drying Process - Robin Ostermeier; Oleksii Parniakov; Stefan Töpfl; Henry Jäger (Foods, 2020)
Available literature and previous studies focus on the Pulsed Electric Field (PEF) parameters influencing the drying process of fruit and vegetable tissue. This study investigates the applicability of PEF pre-treatment considering the industrial-scale drying conditions of onions and related quality parameters of the final product. First, the influence of the PEF treatment (W = 4.0 kJ/kg, E = 1.07 kV/cm) on the convective drying was investigated for samples dried at constant temperatures (65, 75, and 85 °C) and drying profiles (85/55, 85/65, and 85/75 °C). These trials were performed along with the determination of the breakpoint to assure an industrial drying profile with varying temperatures. A reduction in drying time of 32% was achieved by applying PEF prior to drying at profile 85/65 °C (target moisture ≤7%). The effective water diffusion coefficient for the last drying section has been increased from 1.99 × 10−10 m2/s to 3.48 × 10−10 m2/s in the PEF-treated tissue. In case of the 85/65 °C drying profile, the PEF-treated sample showed the highest benefits in terms of process efficiency and quality compared to the untreated sample. A quality analysis was performed considering the colour, amount of blisters, pyruvic acid content, and the rehydration behavior comparing the untreated and PEF-treated sample. The PEF-treated sample showed practically no blisters and a 14.5% higher pyruvic acid content. Moreover, the rehydration coefficient was 47% higher when applying PEF prior to drying.